Empowering EFL learner’s Self-efficacy through Collaborative task-based Instruction: A Critical Review - Sahril Nur; Ranta Butarbutar (VELES Voices of English Language Education Society, 2022)
Self-efficacy is the belief that someone can do work successfully. The study purposes to explore whether collaborative task-based instruction (TBI) can empower EFL self-efficacy? The study uses a critical review, content analysis, and interpretation regarding five perspectives namely in terms (1) cognitive-interactionist, (2) psycholinguistics, (3) sociocultural, (4) psychological, and (5) educational. The results note TBI is effective to use to empower EFL learners’ self-efficacy. And, psychological perspective is the most significant to use.